2016
DOI: 10.1186/s40348-016-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles of endoplasmic reticulum stress sensors in bacterial infection

Abstract: Bacterial infection often leads to cellular damage, primarily marked by loss of cellular integrity and cell death. However, in recent years, it is being increasingly recognized that, in individual cells, there are graded responses collectively termed cell-autonomous defense mechanisms that induce cellular processes designed to limit cell damage, enable repair, and eliminate bacteria. Many of these responses are triggered not by detection of a particular bacterial effector or ligand but rather by their effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…The role of ER stress in microbial clearance has been mostly examined in epithelial cells or mouse myeloid cells, with mechanisms mediating this clearance still incompletely defined. Previous studies found that different branches of ER stress can either enhance or inhibit microbial growth depending on the microbe, infection conditions, or the host species (Pillich et al, 2016). We find that in NOD2-stimulated human MDMs, ER stress leads to enhanced bacterial clearance.…”
Section: Discussionsupporting
confidence: 46%
“…The role of ER stress in microbial clearance has been mostly examined in epithelial cells or mouse myeloid cells, with mechanisms mediating this clearance still incompletely defined. Previous studies found that different branches of ER stress can either enhance or inhibit microbial growth depending on the microbe, infection conditions, or the host species (Pillich et al, 2016). We find that in NOD2-stimulated human MDMs, ER stress leads to enhanced bacterial clearance.…”
Section: Discussionsupporting
confidence: 46%
“…27 Both TLRsignaling and IRE1-mediated splicing of Xbp1 have been shown to invoke innate immune responses and the production of inflammatory cytokines. 27,36,45,60 Our data demonstrated that inhibiting IRE1α attenuates S aureus-induced cytokine production in vivo (mouse model of endophthalmitis) as well as in cultured microglia, implicating its role in regulating the inflammatory innate immune response. The experiments using BMDM from myeloid cell-specific IRE1 −/− mice further validates these findings by showing inhibition of S aureus-induced inflammatory mediators.…”
Section: F I G U R Ementioning
confidence: 59%
“…Bacterial infections have been shown to trigger an UPR 35,36 resulting in the activation of the ER-transmembrane protein IRE1α. Although multiple targets for the IRE1α endonuclease have been identified, the splicing of Xbp1 mRNA is the main under infectious and inflammatory conditions.…”
Section: Er Stress Is Induced During S Aureus Endophthalmitismentioning
confidence: 99%
“…The workshop has also discussed the more global defects at the cellular levels such as in celiac disease, microvillus inclusion disease, or cystic fibrosis which also elicit chronic diarrhea [ 7 9 ]. Altogether, these disorders lead to substantial alterations of the intestinal microbiota and may alter and disturb the finely tuned intestinal hemostasis [ 10 ]. In fact, the gut mucosa is continuously exposed to bacterial and dietary antigens found in the lumen and microbial infections can stress and regulate the epithelial cell integrity and physiology.…”
Section: Editorialmentioning
confidence: 99%